Urban Territorialities: An Introduction (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
The studies collected in this monographic issue intend to revisit an important research topic, with results hitherto scattered in multiple venues, and to refocus on different aspects of urban territoriality in the late Middle Ages from new perspectives. The six essays offer both a general overview, in particular of north‐central Italian cities, and single case studies: Naples and Genoa are two largely comparable realities; the Florentine case is considered during the years of the Ciompi tumult, while that of Avignon provides insights for comparison with some Italian cities.